An Analysis on The Use of English Speech Acts Function by The Staff of Home Stay at Belumbang Tourism Village in Tabanan , Bali - Widhiastuty, Ni Luh Putu Sri; Murdana, I Ketut (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
The purpose of the present research was to analyze the use of English speech acts functions by the staff of home stay at Belumbang Tourism Village in Tabanan Bali. The research method applied was descriptive qualitative approach which was largely relied on the philosophy of phenomenology approach. The types of data were the qualitative ones which were in the forms of words, phrases, expressions, and sentences on the use of English speech functions. The sources of data were primary data which were directly collected from the respondents and the key informant, and the secondary data which were collected from the existing data provided by the second party. The methods used for data collection were observation, questionnaires, and interview methods. The methods for data analysis were descriptive and qualitative by using the theory of speech acts functions proposed by Searle (1983). The population of the research was 30 people. The sampling technique applied was non-probability sampling.  The findings of the research were the result and the discussion showed that those 5 speech act functions, such as: assertive, directives, expressive, commissive, and declarative were used.